Protein conformational flexibility modulates kinetics and thermodynamics of drug binding - M. Amaral (Nature Portfolio, 2017)
An understanding of the dynamics of drug binding and unbinding processes is important for drug discovery. Here, the authors give insights into the binding mechanism of small drug-like molecules to human Hsp90 by combining thermodynamics and kinetics studies as well as molecular dynamics simulations.